Safety and efficacy of electrophysiological studies and radiofrequency ablation of paroxysmal supraventricular tachycardia - Monib, Abdul Khaliq; Nepal, Rajesh; Dhungana, Sahadeb Prasad; Raut, Roshan (Birat Journal of Health Sciences, 2020)
Introduction: Cardiac electrophysiological study (EPS) and radiofrequency ablation (RFA) is an established mode of treatment either as first-line or for drug-refractory arrhythmias. Our center has recently started this service under 2-D mapping outside Kathmandu valley Objective: The aim was to evaluate the safety and efficacy of EPS and RFA for paroxysmal supraventricular tachycardias (PSVT). Methodology: This is an observational prospective study carried out in the Cardiac Unit of Nobel medical college, Biratnagar, Nepal. All cases diagnosed to have PSVT based on electrocardiogram or Holter recordingfromAugust 2018 and May2019wereincluded in the study. Data on clinical profile and findings of EPS were recorded. Fifty-nine cases were chosen for safety and efficacy analysis, using SPSS statistical software version 19. Results: There were 59 patients, 28(47.5%) males, and 31(52.5%) females. The mean age was 38.2 ± 15.9 years. Fifty-three patients underwent RFA while 6 patients underwent only EPS. In the Atrioventricular nodal reentry tachycardia (AVNRT) group, there was female dominance (P=0.2) while in Atrioventricular reentry tachycardia (AVRT) group, there was no significant gender difference (p=0.4). Left-sided pathway (68%) was more common in the AVRT group. Among the left accessory pathway (AP), left lateral AP (44%) was more common. No major complications including death were noted. Two cases of successful ablation relapsed in one month follow up. Conclusions: Early results of this small study in patients with PSVT confirm the efficacy and safety of RFA in newly established electrophysiology (EP) laboratory.